MITIGATION STRATEGIES FOR THE EFFECTS OF CLIMATE CHANGE ON ROAD INFRASTRUTURE IN LAGOS STATE - Nkem Ede, Anthony; Oshiga, Kehinde (European Scientific Journal, ESJ, 2014)
Global climate change-induced effects form part of the principalchallenges confronting mankind in the recent years. The world is becomingmore conscious of the fact that our ecosystem is not adapting naturally to thestresses caused by excessive and uncontrollable human activities. Manyknown effects of climate change on some sectors of the economy are alreadyreceiving appropriate evaluations with mitigation strategies being proffered.Some other areas of the economy, especially in the developing nations arescarcely considered. One of such area is the road infrastructure sector. Inspite of the importance of transportation as a key driver and enabler of theeconomy, little research has been conducted around the world on howvulnerable it will be to climate change. Any unforeseen damage caused byclimate change on the few and insufficient road infrastructure of developingnations will negatively impact the economy and severely retard economicgrowth.For these reasons, this research focuses on the consequences of globalclimate change on the road infrastructure network in Lagos State (Nigeria)and its mitigation strategies. Data from the Nigeria Meterological Agency(NIMET) such as rainfall, temperature, relative humidity and pressure wereanalysed. Regression analysis was applied for predictions. However, theresults obtained confirm that the road infrastructure in Lagos State isexperiencing the basic features of climate change which urges for urgentmitigation and adaptive measures.